Development and characterization of novel jGCaMP8f calcium sensor variants with improved kinetics and fluorescence response range - Tran, Oanh; Hughes, Holly J.; Carter, Tom; Török, Katalin (Frontiers in Cellular Neuroscience, 2023)
Introduction Genetically encoded biosensors for monitoring intracellular calcium changes have advanced our understanding of cell signaling and neuronal activity patterns in health and disease. Successful application of GCaMP biosensors to a wide range of biological questions requires that sensor properties such as brightness and dynamic range, ligand affinity and response kinetics be tuned to the specific conditions or phenomena to be investigated. Random as well as rational targeted mutations of such sensor molecules have led to a number of important breakthroughs in this field, including the calcium sensors GCaMP6f and GCaMP6fu. jGCaMP8f of the most recently developed generation is promising a step-change in in vivo imaging with further increased fluorescence dynamic range. Here, we critically examine the biophysical properties of jGCaMP8f and report development by rational design of two novel variants of jGCaMP8f. Methods We determined the in vitro biophysical properties of jGCaMP8f and selected variants by fluorescence spectroscopies and compared their performance monitoring intracellular Ca2+ transients with previously developed fast and bright GCaMP sensors by live cell imaging. Results We demonstrate that the physiologically highly relevant Mg2+ not only majorly affects the kinetic responses of GCaMPs but also their brightness and fluorescence dynamic range. We developed novel variants jGCaMP8f L27A which has threefold faster off-kinetics and jGCaMP8f F366H which shows a ∼3-fold greater dynamic range than jGCaMP8f, in vitro as well as in HEK293T cells and endothelial cell line HUVEC in response to ATP stimulation. Discussion We discuss the importance of optimization of biosensors for studying neurobiology in the context of the novel variants of jGCaMP8f. The jGCaMP8f F366H variant with a large dynamic range has the potential to improve in vivo imaging outcomes with increased signal-to-noise ratio. The L27A variant with faster kinetics than jGCaMP8f has larger cellular responses than previous fast GCaMP variants. The jGCaMP8f generation and novel improved variants presented here will further increase the application potential of GECIs in health and disease.